Polarographic Study of Cd(II) and Zn(II) Complexation with Solochrome Mordant Dyes - Gupta, P.N.; Raina, Anju (Asian Journal of Chemistry, 2010)
Present communication reports complexation behaviour of solochrome yellow 2GS, solochrome black WDFA, solochrome fast navy 2RS and solochrome dark blue B150 with Cd(II) and Zn(II) studied polarographically at temperatures 25º,35º and 45º. Thermodynamic functions have been calculated to intepret results. Aggregation is overruled by the presence of tetramethyl ammonium perchlorate; monomeric form of dye established, subsequently the equilibrium between metal ligand is made reliable and reproducible.